Floating Food City integrated farming system facility in the freshwater of Laguna de Bay - Sagun, Siddharta S. (College of Architecture, University of the Philippines Diliman, 2023)
As the demand for healthy, nutritious, and sufficient food continues to rise, the country faces a significant risk of future food insecurity due to the ongoing decline in agricultural productivity and production. As the economy shifts its focus away from agriculture to other industries, the existing local farming practices are no longer adequate to sustain agricultural output for its people. The Laguna de Bay basin, which serves as a crucial source of food, water, and livelihood for residents, is also affected by the challenges faced by the agricultural sector. The decrease in agricultural productivity and production can be attributed to various factors, including a decrease in the amount of land used for farming along the lakefront and the challenges faced by each sub-sector within agriculture. Thus, using the concept of floating architecture, this study presented a sustainable alternative solution of a floating integrated farming development as a viable system of food production, to address the challenges of food insecurity. Given that it is optimal to construct them in locations where food is more important and run by more advanced technology, the concept of the floating farm is to be introduced. This study explores the concepts of transparency, evolution, and familiarity by incorporating design objectives centered around three key principles: smart, green, and resiliency. It employs a framework rooted in the pillars of sustainability: social, environmental, and economic. By creating these strategies and approaches, the final architectural design solution of the proposed floating farm facility integrates innovative design and technology on building structure, materials and interactive spaces. Additionally, the design takes into account various factors like building codes, site conditions, zoning, and local regulations.